2016
DOI: 10.1017/s0016756816000844
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous ostracods from central Honshu, Japan

Abstract: Silicified beyrichiocopid and podocopid ostracods from limestone nodules derived from the middle part of the Ichinotani Formation within the Hida Gaien Terrane of central Honshu Island, Japan, are associated with fusulinid foraminifera that indicate strata of the middle Moscovian (Pennsylvanian, Carboniferous). This is a rare record of ostracods from the Palaeozoic of Japan and the first systematic description of ostracods from the Carboniferous of the Hida Gaien Terrane. The fauna comprises six ostracod speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, an Ordovician age for that assemblage must be regarded as unproven. The ostracods in question were recovered from a loose block of mudstone, not from outcrop; both Devonian and Carboniferous ostracods are known from the Ichinotani Valley (Stocker et al, ; Tanaka, Siveter, & Williams, and references therein); and based on the published figures (drawings) of the ostracods the taxonomy of the valves depicted requires detailed reassessment. Our pilot studies have determined that undoubted Silurian ostracods do occur in Japan, and we present the results herein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an Ordovician age for that assemblage must be regarded as unproven. The ostracods in question were recovered from a loose block of mudstone, not from outcrop; both Devonian and Carboniferous ostracods are known from the Ichinotani Valley (Stocker et al, ; Tanaka, Siveter, & Williams, and references therein); and based on the published figures (drawings) of the ostracods the taxonomy of the valves depicted requires detailed reassessment. Our pilot studies have determined that undoubted Silurian ostracods do occur in Japan, and we present the results herein.…”
Section: Introductionmentioning
confidence: 99%
“…Kuwano, 1987), Carboniferous (e.g. Stocker et al, 2016) and Permian (e.g. Tanaka, Ono, Yuan, Ichida, & Maeda, 2012) ostracods are documented from Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18). Stocker et al (2016) first reported a "Eiferian mega-assemblage" from central Japan (the Middle Moscovian Ichinotani Formation) composed of Amphissites, Kirkbya, Bairdia, Aechmina, and Healdia. The Eiferian mega-assemblage Journal of Paleontology 97(S92):1-33 typically represents high-energy turbulent conditions in a shallow carbonate platform setting (Becker, 1971).…”
Section: Paleoecology Of Ostracodes From the Nagaiwa Formationmentioning
confidence: 99%
“…Here, I examined podocopes because Recent species are demonstrably useful for defining biogeographical regions (Titterton and Whatley, 1988;Tanaka, 2008) and therefore they are important taxa for reconstructing paleogeography (Schallreuter and Siverter, 1985;Williams et al, 2003;Perrier and Siveter, 2014;Tanaka et al, 2019; but see Pour et al, 2011;Mohibullah et al, 2012). In Japan, some Paleozoic ostracodes were described from Southwest Japan (Kuwano, 1987;Tanaka et al, 2012Tanaka et al, , 2013Tanaka et al, , 2018Tanaka et al, , 2019Stocker et al, 2016;Siveter et al, 2018). However, little is known about Paleozoic ostracodes from Northeast Japan, and all the existing works were written before the 1970s using optical photographs only (Ishizaki, 1963(Ishizaki, , 1964a(Ishizaki, , b, 1967(Ishizaki, , 1968).…”
Section: Introductionmentioning
confidence: 99%